(untitled) (Entrepreneurship Journal for Finance and Business, 2023)
The problem of the study stems from the fact that the relationship, whether effect or causation, is not fixed between fiscal policy and economic performance variables, including economic growth and unemployment, as it differs from one country to another, and from time to another time depending on the nature of the economies under study, The study aims to verify empirically about the impact of fiscal policy tools on economic growth and unemployment with determining the direction of the causal relationship of these variables in Jordan for the period (1990-2021). The study used models (Cointegration) for the long-term relationship and vector error correction models (VECM) for the short-term relationship and (Granger) test for the causal relationship. the study concluded that the effect of government consumption spending is negative on economic growth and unemployment, and there is no effect of government investment spending on either economic growth or unemployment, with a causal relationship from government spending, especially consumption, to both economic growth and unemployment, as it found That taxes have a positive effect on economic growth and do not affect unemployment with a causal relationship from taxes to economic growth and unemployment, while the causal relationship was from taxes on income to economic growth and from customs taxes and foreign trade to unemployment, while the causal trend was from economic growth to taxes customs duties and to taxes on foreign trade, these results support the neoclassical point of view in terms of the relationship of influence and support Keynesian law at the expense of Wagner’s law regarding causation. As for public debt, its impact was negative on economic growth and positive on unemployment, and the direction of the causal relationship was from debt to economic growth only.